Application of arterial spin labeling perfusion MRI to differentiate benign from malignant intracranial meningiomas. Issue 97 (December 2017) - Qiao, Xin J.; Kim, Hyun Grace; Wang, Danny J.J.; Salamon, Noriko; Linetsky, Michael; Sepahdari, Ali; Ellingson, Benjamin M.; Pope, Whitney B.
Highlights: ASL CBF maps are processed in patients with intracranial meningiomas. Three perfusion patterns can be characterized by visual evaluation of ASL CBF maps and are in correlation with WHO grades of meningiomas. Qualitative evaluation of ASL CBF maps may prove valuable in differentiating benign from malignant intracranial meningiomas. Abstract: Purpose: Differentiating WHO grade I–III of meningioma by non-invasive imaging is challenging. This study investigated the potential of MR arterial spin labeling (ASL) to establish tumor grade in meningioma patients. Material and methods: Pseudo-continuous ASL with 3D background suppressed gradient and spin echo (GRASE) was acquired on 54 patients with newly diagnosed or recurrent intracranial meningioma. Perfusion patterns characterized in CBF color maps were independently evaluated by three neuroradiologists blinded to patient history, and correlated with tumor grade from histo-pathological review. Results: Three perfusion patterns could be discerned by visual evaluation of CBF maps. Pattern 1 consisted of homogeneous hyper-perfusion of the entire tumor; pattern 2 demonstrated heterogeneous hyper-perfusion; pattern 3 showed no substantial hyper-perfusion. Evaluation of the perfusion patterns was highly concordant among the three readers (Kendall W = 0.9458, P < 0.0001). Pattern 1 was associated with WHO Grade I meningioma of ( P < 0.0001). Patterns 2 and 3 were predictive of WHO Grade II and III meningioma ( P < 0.0001), with an odds ratio ( OR, versus pattern 1) of 49.6 ( P < 0.01) in a univariate analysis, and an OR of 186.4 ( P < 0.01) in a multivariate analysis. Conclusion: Qualitative evaluation of ASL CBF maps can help differentiate benign (WHO Grade I) from higher grade (WHO Grade II and III) intracranial meningiomas, potentially impacting therapeutic strategy.